ANTHROPOMETRY AND ITS RELATIONSHIP WITH THE POWER ANAEROBIC alactic (AAP) PLAYERS IN BASKETBALL GAME FOLLOWING THEIR POSITIONS - طوبال أمين; منصور بن لكحل (Journal of Sport Science Technology and Physical Activities, 2025)
This research is done to know the relationship between some anthropometric measurements and alactic anaerobic power (AAp) in basketball players (U19) according to their positions in the game. And it was assumed that there is a difference in the relationship following each position taken apart; and this to answer the following questions: What are the most important anthropometric measures that have a relationship with the AAP among basketball players according to their playing positions? To prove our assumption, we selected a sample of 61 players representing five junior teams playing in Super Algerian division of basketball for the sports season 2012/2013. These players were chosen randomly from a set consisting of 240 players, knowing that the championship has 20 teams. For this, the descriptive analytical method was used. There was thus collected data using the necessary anthropometric measures and testing of the vertical expansion of the AAP. Then we proceeded to the statistical treatment of data with (MOYENNE-ECARTYPE - FormulE OF Person) And it was concluded that: 1-There is a strong and positive relationship between size and the AAP for the position of (play maker). 2-There is a strong and positive relationship between the weight and the AAP (Play Maker - CENTER – POWER FORWARD). 3-There is a significant positive relationship between the perimeter of the forearm and the AAP (SHOOTING GURD – Small Forwarrd - CENTER - POWER FORWARD ). That is why we insisted on the need to use anthropometry, including that of the perimeters during selection saw his powerful relationship with the AAP.